HIV Risk Assessment and Risk Reduction Strategies in the Context of Prevailing Gender Norms in Rural Areas of Cabo Delgado, Mozambique. (February 2013) - Bandali, Sarah
Since minimal information exists on how individuals work within existing social norms to reduce HIV risk, this study explored the specific factors influencing men and women to reduce their HIV risk in the face of prevailing gender norms in rural villages of Cabo Delgado, Mozambique. Qualitative data were gathered from 160 participants through 29 in-depth interviews to explore gender norms, HIV risk determinants, and risk reduction responses. Results were analyzed using adaptations of grounded theory and constant comparative analysis. Men and women who actively take measures to decrease their risk of HIV infection associate a partner's acceptance of condom use and an HIV test as confirmation of emotional intimacy in the relationship. Other factors influencing risk reduction efforts include various levels of influence from family or peers, prior experience, relationship dynamics, and a reflection of broader personal outcomes.